MANIFESTAÇÕES DE PODER E IDENTIDADE EM TORNO DA LÍNGUA UCRANIANA EM PRUDENTÓPOLIS - Costa, Lourenço Resende da (2013)
The aim of this study is to detect how the use of the Ukrainian language and the discipline of Ukrainian language are presented as demonstrations of power and identity in the town of Prudentópolis. The main focus of analysis is centered in the community of Ligação, which is in the countryside, and in the Imaculada Conceição State School, located in the same place. The so-called establishment is the only state school in Prudentópolis which comprises the discipline of Ukrainian language in its course program. In addition, the Ligação place has a significant number of inhabitants who are Ukrainian descendents. Therefore, this is a place where it becomes possible to analyze how the Ukrainian identity and the relations of power become effective. The theoretical analysis is based on the discussions over power, mainly from Faulkner’s point of view. The concept of identity, under the perspective of several authors, will help us think over the Ukrainian ethnic identity in Ligação. The concepts of strategy and tactics, with basis on the Certonian perspective, will allow us to think about the asymmetrical relations in the region of the community where the Imaculada Conceição School is inserted. The sources are both, spoken and written. The spoken sources were taken from inhabitants of Ligação, as well as the head and teachers of the school. The written sources refer to official documents of the school and the Office of Education in the State of Paraná. With regards to immigration, besides the specialized bibliography, decrees and laws concerning the process of immigration were also used.